(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Gold has always been considered as a sacred item in the Hindu way of life. The prices of gold have risen very fast during the last decade. It generally happens that whenever price of a commodity increases, its demand decreases, but in case of gold it is not true. The prices of gold have increased and at the same time demand has also increased in India. In this paper titled, “Indian’s Liking for The following are the limitations of the study.Gold and Causes for Rising Prices of Gold”, an attempt has Indians, Hittites, Chinese, and others. 1 been made to find out why Indians are so much attached to gold. It has been observed that gold is much more just than a precious metal for Indians. There are such Indian customs that require buying of gold for special occasions such as Diwali, Dhanteras, Akshay Tritiya etc. The liking for gold is so deep in India that gold jewellery is transferred from grandmother to mother, mother to daughter and so on. The research paper will also throw light on various factors that are responsible for increase in the price of gold. It has been found that investment in gold has been found safe even in the inflationary periods. Gold worldwide has been accepted as a safe store of value. The supply of gold cannot be increased very much at any price because it is still difficult and costly to discover gold. Real estate market and bank failure also affect price of gold.